Inter-firm linkages and the wealth effects of financial distress along the supply chain☆ - HERTZEL, M; LI, Z; OFFICER, M; RODGERS, K (Journal of Financial Economics, 2008)
Extant research examines the extent to which bankruptcy has intra-industry valuation consequences. This study broadens the investigation by examining the wealth effects of distress and bankruptcy filing for suppliers and customers of filing firms. On average, important wealth effects occur prior to and at bankruptcy filings and extend beyond industry competitors along the supply chain. Specifically, distress related to bankruptcy filings is associated with negative and significant stock price effects for suppliers. Supplier wealth effects are more negative when intra-industry contagion is more severe. We also investigate the importance of industry structure, specialized product nature, and leverage on supply chain effects.